2021
DOI: 10.1002/srin.202100232
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gradient Alloy Steel with Quasi‐Continuous Ratios Fabricated by Selective Laser Melting: Microstructure and Corrosion Behavior

Abstract: In this article, a quasi‐continuous ratio gradient alloy steel (GAS) with a 24CrNiMo high‐strength low‐alloy steel matrix for high‐speed railway brake discs is fabricated by selective laser melting (SLM). The composition of GAS is X% 24CrNiMo + (1–X)% wear‐resistant stainless steel (WSS), in which X is 100, 65, 35, and 0. The relationship between the microstructure and the corrosion resistance is intensively studied by electron backscatter diffraction (EBSD) and potentiodynamic electrochemical equipment. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…As can be seen obviously, the reactions (2) and (3) are spontaneous owing to the negative Gibbs free energy in the range of temperature. In addition, the Δ G of reaction (3) is much lower than that of reactions (2) and (4), indicating that the Cr 23 C 6 phase is the thermodynamically favoured products and it is a higher possibility of preferential formation and precipitation [17]. The G5 exhibits similar phase constituents including bcc α-Fe and Cr 23 C 6 phase before and after heat treatments owing to the addition of high Cr content stainless steel to synthesise enough Cr 23 C 6 during LMD process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen obviously, the reactions (2) and (3) are spontaneous owing to the negative Gibbs free energy in the range of temperature. In addition, the Δ G of reaction (3) is much lower than that of reactions (2) and (4), indicating that the Cr 23 C 6 phase is the thermodynamically favoured products and it is a higher possibility of preferential formation and precipitation [17]. The G5 exhibits similar phase constituents including bcc α-Fe and Cr 23 C 6 phase before and after heat treatments owing to the addition of high Cr content stainless steel to synthesise enough Cr 23 C 6 during LMD process.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wang et al [16,17] successfully prepared a quasi-continuous ratio gradient alloy steel from 100% 24CrNiMo substrate to 100% a stainless steel by selective laser melting (SLM) for high-speed railway brake discs. The results showed that corrosion current of gradient alloy steel is 1% of 24CrNiMo substrate and wear rate is 34.8% of 24CrNiMo substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The structural characteristics of the corrosion products, especially the surface morphology, therefore play a vital role in the corrosion behavior. [ 46–48 ] Figure 3 shows the macroscopic surface morphology of the corrosion products formed after different durations of immersion. Figure 3a,b show that two types of surface morphology appeared on the specimen surface after immersion for 24 and 72 h. The partial area of the specimen surface obtained after 24 h of immersion was covered with corrosion products.…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion mainly occurs in dendrites, indicating that the corrosion type is typical intergranular corrosion. According to the reference [45], the corrosion products in the alloy are mainly produced in the following ways in 3.5 wt-% NaCl solution: However, is unstable and further decomposed according to the following equation:
Figure 11 High-magnification corrosion morphology after dynamic potential polarisation test in 3.5 wt-% NaCl solution and element distribution of Nb0.3 HEAC.
…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion mainly occurs in dendrites, indicating that the corrosion type is typical intergranular corrosion. According to the reference [45], the corrosion products in the alloy are mainly produced in the following ways in 3.5 wt-% NaCl solution:…”
Section: Corrosion Morphologymentioning
confidence: 99%